Tongues on fire Caribbean lesbian lives and stories - Elwin, Rosamund (Women's Press, 2008)
In Tongues on Fire, Caribbean lesbians speak zami desire honestly and eloquently, loudly and clearly. Narrating their life stories, they claim what has never been acknowledged―lesbian history and continuity in the Caribbean. They collectively honour that history and continuity in fiction sweet with intimacy, sensuality, and memory. Like the lives and stories of Caribbean lesbians, Tongues on Fire is unique. Rosamund Elwin has put together a fine collection that includes well-known writers such as Michelle Cliff, Shani Mootoo, and Makeda Silvera.
Keywords: amériques; arts; caraïbes; discipline; histoire et politique; personnes lesbiennes; ressource en ligne; roman; régions géographiques; sexualité; thématiques; émotions; études littéraires

"Eskimo chicks and word warriors": The creative cultural spaces of Elisapie Isaac and Taqralik Partridge - Foot, Johanna Maria (Université Carleton, 2008)
For this study, I have interviewed fourteen women composers of electroacoustic music in or near the three Canadian urban centres of Montreal, Toronto, and Vancouver. Montreal: Ciaire Pich6, Lucie Jasmin, Pascale Trudel, Monique Jean, Helen Hall and Kathy Kennedy; Toronto: Gayle Young, Sarah Peebles, Wende Bartley, Elma Miller, Ann Southam, and Carol Ann Weaver; Vancouver: Hildegard Westerkamp and Susan Frykberg. These interviews were all conducted between January and November of 1993. References to the development of electroacoustic music in Canada are sparse in the existing literature, both in general histories of electroacoustic music, and in histories of Canadian music. And even though there seem to be some areas of change (for instance, recent publications in Quebec), women composers are under-represented in writings and recorded collections of electroacoustic music in Canada. Chapter Two situates the work of women composers in the Canadian scene, discussing particularly the work of Norma Beecroft, Marcelle Desch§nes, Diana McIntosh, and Micheline Coulombe Saint-Marcoux. Chapter Three describes the metaphors, images and myths invoked in malestream discourses associated with electroacoustic music, in popular magazines, course texts and software. I investigate how my consultants’ language reflects and/or contests mainstream imagery, or how it might be framed by entirely different assumptions and experiences. Chapter Four is concerned with the institutional structures of electroacoustic music. I discuss how gendering exhibits itself in the division of labour in electroacoustic studio courses at universities, as well as in concert halls, conferences, and professional organizations. Excerpts from the interviews record my consultants experiences in these institutions, as students, teachers, and composers. In Chapter Five, I point out the variety of strategies that each composer uses to construct her identity within the world of electroacoustics. Each entry takes the form of a three or four page sketch, with quotes from the interview regarding the social environment, equipment choices, compositional styles, and particular pieces that my consultant discusses. Chapter Six discusses three pieces in detail: one by Susan Frykberg, Woman and House; one by Wende Bartley, A Silence Full of Sound; and one by Hildegard Westerkamp, Breathing Room. I focus on how each of the composers chooses to work with technology, and how her culturally-constructed position as a woman affects her work. I describe how my consultants imagine other stories to tell, and other possible lived social relations. The conclusions in Chapter Seven, in addition to suggesting areas for future research, discuss three themes that run throughout the study: the idea of gender as performance, the doubleness of my consultants' responses to technology, and the importance of the linguistic and musical metaphors that they use.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; arts; canada; discipline; femmes* autochtones; mémoires/thèses; périodes historiques; régions géographiques; thématiques; écriture des femmes*; études littéraires

Decoding Black Women: Policing Practices and Rape Prosecution on the Streets of Philadelphia - Irving, Toni (NWSA Journal, 2008)
Black women are generally displaced as victims of rape. The police response to the sexual assault of black women in general and lower-class black women in particular is illustrative of how sexual ideologies help construct complex social hierarchies that in turn structure rights. How the law currently deals with rape places black women outside of the narrative frames that legitimate entitlement. Rape continues to stand in for, and effectively obscure, other social, political, and economic concerns. Unpublished and often ignored, the rape narrative is a ripe site to supply oppositional interpretations of national experience and transmit some of the structural problems in the criminal justice system. Pulling from over two thousand “real” rape cases of low-income black women ignored and not investigated in Philadelphia between 1995 and 2000, this article reads black female rape narratives as case studies in order to discuss the way personal narratives of rape victims are structured by competing and overwhelming sociolegal narratives that undercut their reception. As the fastest growing prison population, the presence of the law to punish black women stands in stark contrast to the absence of the law to protect them.
Keywords: 1900-1999; 1990-1999; afro-féminisme; amériques; approches et analyses; arts; corps; cours; discipline; droit; droit des femmes* noires; droits des femmes*; féminisme afroaméricain; histoire et politique; intersectionnalité; inégalités; philadelphie; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; science politique; science politique et droit; sex2283; sexisme; systèmes d'oppressions; thématiques; viol; violences; états-unis; études littéraires

Épistémologie du placard - Sedgwick, Kosofsky Eve (Éditions Amsterdam, 2008)
Lorsqu’il fut publié pour la première fois aux États-Unis en 1990, Épistémologie du placard devint immédiatement un classique qui, aux côtés des travaux de Judith Butler et de Teresa de Lauretis, posa les termes de la « théorie queer ». À mi-chemin entre les études féministes et les gay and lesbian studies, Eve Kosofsky Sedgwick déconstruit la sexualité comme Butler le genre. Dans cet ouvrage de référence, elle affirme que l’ensemble de la culture occidentale moderne s’articule autour de l’opposition homo/hétérosexuel et que celle-ci affecte les binarismes qui structurent l’épistémologie contemporaine, de savoir/ignorance à privé/public en passant par santé/maladie.S’appuyant sur de nombreux textes datant de la fin du XIXe et du début du XXe siècles (Wilde, Proust, Nietzsche, Melville et James), l’auteur traque l’émergence des nouveaux discours institutionnels médicaux, juridiques, littéraires et psychologiques, qui produiront en miroir les figures de « l’homosexuel » et de « l’hétérosexuel », au détriment des multiples différences au cœur des sexualités.
Keywords: amériques; approches et analyses; arts; cours; cycles supérieurs; discipline; fem1000; fem7000; lit2815; lit3220; lit3495; lit4700; premier cycle; queer; régions géographiques; sciences humaines; sexualité; soc2014; thématiques; épistémologie; états-unis; études littéraires